Tsarevich on the journey through Europe: Alexander Nicolaevich and his correpondence with the Tsar Nicholas I, 1838–1839 (Theatrum historiae, 2013)
Alexander Nicolaevich, the heir of the Russian imperial throne, later the Emperor Alexander II (ruled 1855–1881), made a long journey through Europe in 1838–1839. Article, based primarily on the correspondence between Alexander and his father Nicholas I, is focused on this journey as a part of the prince’s preparation for his future reign, in the context of the other journeys of the Romanov family and Russian nobles through Europe.